Preparation And Characterization Of Polyurethane Composites Reinforced By Kenaf Core - Bakar, Azizah Abu (2018)
In this study, the effect of silane treatment on kenaf core (KC) and KC reinforced polyurethane (KCP) composites were discussed. The composite was prepared using one shot process. Firstly, polyurethane (PU) was prepared from methylene diphenyl diisocyanate (MDI) and glycerol using different NCO/OH ratio and KCP composites with different KC loadings were prepared using a suitable NCO/OH ratio. From the mechanical properties measurement, it was found that NCO/OH ratio of 1.5 and KC loadings of 20% were suitable to be studied. In the next phase, KC was treated with different types of silane (1 – 3%); which were vinyltrimethoxysilane (VTMS), trimethoxyphenylsilane (TMPS), and tetramethoxy orthosilicate (TMOS) using hydrolysis method with ethanol/water (80:20 volume) as silanization medium for KC The properties of untreated KC (UKC) and treated KC (TKC) were investigated through filler morphology analysis, Scanning Electron Microscopy – Energy Dispersive X-ray (SEM – EDX) mapping element analysis, Fourier Transform Infrared (FTIR) analysis, and Thermogravimetric Analysis (TGA) analysis. UKC and TKC surface morphology and SEM – EDX mapping analysis showed the presence of Si element on the TKC surface. Thermal analysis revealed that, silane treatment had enhanced the thermal stability. The visco-mechanical properties of kenaf core treated with silane – polyurethane (TKCP) composite were measured by Dynamical Mechanical Analysis (DMA).